Assessment of the Quality Indicators Interconnection of Transport Services while Cargo Transportation - KUNDA, Neonila T.; LEBID, Victoriia V. (Journal of Advanced Research in Law and Economics, 2019)
Quality assurance of transport services is one of the main ways of increasing the efficiency of international freight transportation. Assessing the level of transport services is a complex and time-consuming process that requires new approaches. The use of the mathematical apparatus of fuzzy set theory and the use of a linguistic variable makes it possible to form a comprehensive quality index based on incomplete and inaccurate information obtained by expert means. Such an indicator may be the ‘attractiveness of the route’. An expert system is presented in which the quality assessment of the route is made according to the formal rules of fuzzy logic. A mathematical model of transport service quality management was constructed to select the driving route according to the criterion of ‘route attractiveness’, which was compiled according to the rules of Mamdani's inference. Compatibility functions for Ukrainian sections of international transport corridors (ITCs) have been obtained, and schedules of attractiveness of the route according to the investigated ITCs have been constructed. The Hamming distance metric and the Bellman-Zadeh approach were used to test the convergence of the study results. The presented model allows to take into account the requirements and to harmonize the interests of the participants of the freight transportation process regarding the quality of transport service.